ANALISIS KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA BANK BUMN - Sofyan Marwansyah (Universitas Bina Sarana Informatika, 2016)
High and low value of a company is determined by the stock price of the company, the better the stock price of a company, the higher the value of a company and to see the stock price of a company can be judged from the company's financial performance. In the economy of a country must be supported by the good performance of the banking public and private. In this study the authors will perform analysis of the financial performance of banks Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Return on Assets (ROA) and the Loan to Deposit Ratio (LDR) on stock price of BUMN the period 2008 to 2015 were obtained from annual report state-owned banks, the analysis techniques that will be used in this research is multiple linear regression to obtain a comprehensive picture of the relationship between the variables and the other variables. The results showed that the variable Return On Asset (ROA) positive and significant impact on stock price of banks, while the Capital Adequacy Ratio (CAR) has positive effect and does not significantly influence stock prices, Non-Performing Loan (NPL) a significant negative effect on stock prices, Loan to Deposit Ratio (LDR) and no significant negative effect on stock price. Simultaneous test results show there is influence between CAR, NPLs, ROA and LDR together to share price state-owned bank. The magnitude of the effect was 82.1%, while the remaining 17.9% influenced by other factors outside the research Keywords : Capital Adequacy Ratio, Non Performing Loan, Return on Assets, Loan to Deposit Ratio, and stock price of Banking